2014
DOI: 10.1007/s11064-014-1457-1
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Promotes Neuronal and Behavioral Recovery by Suppressing Inflammatory Response and Apoptosis in a Rat Model of Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a common and devastating disease affecting millions of people worldwide annually. Exaggerated inflammation and apoptosis are two pivotal pathological processes for secondary brain injury after ICH. Quercetin, a flavonoid widely distributed in various herbs, fruits and vegetables, has been proved to improve neuronal functional recovery in spinal cord injury rats. However, the efficacy of quercetin in caring for post-ICH brain injury has not been investigated. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…It is noted that mNSS was generally used to assess a combination of motor, sensory, and balance functions [23]. Neurological function was graded on a scale of 0–18 (normal score, 0; maximal deficit score, 18).…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that mNSS was generally used to assess a combination of motor, sensory, and balance functions [23]. Neurological function was graded on a scale of 0–18 (normal score, 0; maximal deficit score, 18).…”
Section: Methodsmentioning
confidence: 99%
“…The dose and timing of quercetin were based on previous researches. 15,17 Different set of animals were used to undertake the analyses.…”
Section: Animal Selection and Group Allocationmentioning
confidence: 99%
“…Therefore, it has been used for many diseases, such as focal cerebral ischemia 16 and intracerebral hemorrhage. 17 Previous studies have demonstrated that quercetin can reduce inflammatory lesions and exert neuroprotective effects in the hypothalamus of high-fructose-fed rats via suppressing NLRP3 inflammasome activation. 18 Recently, quercetin has been reported to exert neuroprotective effects by suppressing inflammation in SCI rats.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that mNSS was generally used to assess a combination of motor, sensory, and balance functions [9,22]. Neurological function was graded on a scale of 0-18 (normal score, 0; maximal deficit score, 18).…”
Section: Neurological Function and Brain Edemamentioning
confidence: 99%
“…The brain slices (2 mm thick) of the contralateral and ipsilateral hemispheres and cerebellum were cut. The whole brain water content was calculated from all slices [9,22]. The brain slices were weighed to obtain the wet weight immediately and dried in an oven at 100•C for 24 hrs to obtain the dry weight.…”
Section: Neurological Function and Brain Edemamentioning
confidence: 99%